Exploring immune activation patterns in HER2-low and HER2-ultralow breast cancer subtypes - Munkácsy, Gyöngyi; Santarpia, Libero; Győrffy, Balázs (The oncologist (Dayton, Ohio), 2025)
Abstract Background A deeper understanding of the molecular and clinical characteristics of HER2-low and ultralow breast cancer (BC) subtypes is essential for advancing therapeutic strategies. Methods Three independent GEO datasets with microarray and IHC/FISH data from 510 BC patients were analyzed to establish reliable HER2 expression cutoff values (>3034 for HER2-positivity and <1780 for HER2-ultralow), defining HER2-positive (HER2+), HER2-low, and HER2-ultralow cohorts. Combined with hormone receptor status, six distinct BC subgroups were identified. Prognosis was evaluated using univariate and multivariate survival analysis in a dataset of 7830 BC patients, alongside correlative analysis of 17 immune-related gene signatures across subgroups. A PubMed literature review compared our findings with existing studies. Results In hormone receptor-positive (HR+) patients, HER2-low tumors were associated with better prognosis than HER2-ultralow and HER2+ subgroups (P = .0048 for relapse-free survival (RFS) and P = .0015 for distant-metastasis-free survival (DMFS)). No prognostic significance was observed in HR-negative (HR−) patients. Immune gene activation was consistently higher in HR− tumors, with HER2-low (HR+ and HR−) and HR-/HER2+ patients showing significant immune signature overlap. While HR+/HER2-ultralow and HR+/HER2+ patients had modest immune activation, HR-/HER2-ultralow patients exhibited the strongest association with immune signaling, including IFN signaling, T cell-activating cytokines, and cytotoxic effector molecules. Conclusions These findings, supported by a comprehensive literature review, indicate that patients with HER2-low and HER2-ultralow BC exhibit distinct immune patterns, which supports their classification as unique BC subgroups.